Sistem Pendukung Keputusan untuk Rekomendasi Obat Luar dengan Menggunakan Metode Simple Additive Weighting (SAW) - Rudi Hermawan; Rahman Abdillah; Wawan Hermawansyah; Nur Alam (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2025)
Quality health services are an important factor in increasing patient trust in medical facilities and health workers. One of the crucial aspects is accuracy in providing drug recommendations that suit the patient's needs. Drug recommendations are influenced by various criteria, including effectiveness, safety, price, availability, and potential side effects. However, in practice, there is often a gap between the patient's expectations and the reality of the treatment received. This can affect patient satisfaction and perception of health services. To overcome these challenges, a Decision Support (SPK) is needed that is able to provide drug recommendations in a more objective, measurable, and structured manner. This study uses the Simple Additive Weighting (SAW) method because of its advantages in processing various complex and diverse criteria. SAW works by giving weight to each attribute, normalizing the data, and then calculating the preference value to determine the best alternative from several available drug options. The results of the study show that the SAW method is able to produce more structured and consistent recommendations than manual determination. In this study, the drug with the highest preference value, which is 92.00, was recommended as the top choice. These findings confirm that SPK and SAW-based approaches can be an effective solution in supporting medical personnel, especially in the selection of external drugs. In addition to improving decision accuracy, this SPK also has the potential to be further developed, for example by integrating into an electronic medical record (EMR) or based on a mobile application, so that its use becomes more practical and accessible. Thus, the implementation of the SAW method in SPK not only provides benefits on the technical aspect, but also contributes to improving the quality of health services as a whole.